SINERGITAS AGAMA HINDU DAN BUDAYA BALI: PERSPEKTIF SOSIOLOGI - I Dewa Gede Agus Priana Putra; I Made Hartaka (Jnanasidanta, 2022)
Religion as a cultural system is a pattern for behavior that consists of a series of rules,plans, and instructions that humans use in regulating their actions, which were expressed by anAmerican anthropologist, Clifford Geertz. The organization of understanding that is enshrined insymbols related to the expression of human behavior is understood as culture. Religion can notonly be understood as a set of values outside of humans, but also a system of knowledge and asystem of symbols that can give birth to meaning. Communities in the area have their own culturethat is in accordance with the values of the community's point of view that reflect the community'sview of life. Culture then turns into values and norms that become local culture. Local culture isoften called local wisdom which can be interpreted as a whole including and may be consideredthe same as cultural identity which is translated as the cultural identity or personality of a nation,which results in the nation being more able to absorb and process cultural influences that cometo it. from outside his own area, according to his character and personal needs. The interactionbetween religion and culture has resulted in cultural diversity. Likewise with Balinese culture,which is dominantly influenced by Hinduism, which later will create synergies between the two